Peran Hukum Bisnis dan Economic Analysis Of Law (EAL) dalam Konteks Sumber Daya Manusia Elektronik (E-SDM) Sebagai Legitimasi dan Media Pengelolaan SDM Yang Multiguna di Era Society 5.0 dan Era Digitalisasi di Bidang Pertambangan - Hernawan, Rosyanto Yudha; Susilo, Hendra; Bayu, Benediktus; Budiwaty Budiwaty; Khuzaini Khuzaini; Shaddiq, Syahrial; Fahmanadie, Daddy (Universitas 17 Agustus 1945, 2024)
Current developments in technology and information systems This is progressing quite rapidly. Electronic human resource management (E-HRM) as an organizational unit consisting of personnel who process human resource data using computer and non-computer technology. This study uses the literature review method related to business law (BL), economic analysis of law (EAL), and E-HRM research. Literature sources in this study used books, information sources from official government agencies and international organizations as well as scientific articles accredited by Science and Technology Index (SINTA) or SCOPUS. The search strategy uses keywords related to related topics. E-HRM is the embodiment of the intelligent society 5.0 culture in managing the staffing system. Various scopes of personnel management such as planning, administration, payroll and staff evaluation can be carried out effectively and efficiently in mining industry